A study on the perception to usability of the thoth tool - Charles, Fabienne (2022)
Usability is an extremely important factor for a software, so many studies have been done in relation to the evaluation of usability in web tools. This study, through a Systematic Literature Review, seeks to know which methods, tools for empirical evaluation, and metrics are being used in evaluations, and the limitations found by evaluators. The results of the SRL were support for the methodology conducted in this study, which is of exploratory qualitative nature, where a heuristic evaluation and a usability test were applied to users of Thoth, a web tool for automation of Systematic Literature Reviews. The main purpose was to map the users’ limitations and find heuristic flaws in the tool, in order to catalog them, aiming at a better usability of this system. As a result, we identified that the system violated nine of ten heuristics. According to the severity degrees assigned, error prevention is the most frequent. Concerning the usability test, the opinions were very diverse between the graduate and post-graduate users in terms of ease of adaptation but at the beginning they had almost the same preoccupations.